2014
DOI: 10.1007/s10995-014-1442-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Unhealthy Weight in a National Sample of US Adolescents with Autism and Other Learning and Behavioral Disabilities

Abstract: We estimated the prevalence of obesity, overweight, and underweight among US adolescents with and without autism and other learning and behavioral developmental disabilities (DDs) and assessed the health consequences of obesity among adolescents with DDs. From the 2008 to 2010 National Health Interview Survey, we selected 9,619 adolescents ages 12–17 years. Parent respondents reported weight, height, presence of DDs and health conditions. We calculated body mass index (BMI) and defined obesity, overweight, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
1
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 39 publications
3
80
1
12
Order By: Relevance
“…The elevated obesity prevalence based on nationally representative samples in children with ASD compared with those without the condition has been previously reported by our group 10 and others 9,18,24,25,35 as well as in school-based and clinical samples. 8,[26][27][28]36 Chen et al reported an obesity prevalence of 21.1% among 10-17-year-olds in the 2003 round of NSCH, similar to our estimates, and consistent with a leveling off in prevalence trends over time seen in other nationally representative samples of US children.…”
Section: Discussionsupporting
confidence: 78%
“…The elevated obesity prevalence based on nationally representative samples in children with ASD compared with those without the condition has been previously reported by our group 10 and others 9,18,24,25,35 as well as in school-based and clinical samples. 8,[26][27][28]36 Chen et al reported an obesity prevalence of 21.1% among 10-17-year-olds in the 2003 round of NSCH, similar to our estimates, and consistent with a leveling off in prevalence trends over time seen in other nationally representative samples of US children.…”
Section: Discussionsupporting
confidence: 78%
“…Children with mobility limitations have also been shown to have a higher rate of obesity compared with children without such limitations [19,20]. Children with cognitive limitations such as intellectual disability [21,22], autism [23][24][25][26][27], learning disabilities [19,26], and attention deficit hyperactivity disorder (ADHD) [26,[28][29][30][31] also have an elevated prevalence of obesity. Environmental risk factors contributing to obesity in children in general, such as low socioeconomic status, unhealthy diet, and sedentary lifestyle, may also affect children with disabilities, who may be more susceptible to such factors owing to their physical, cognitive, and other functional limitations [20,21,32].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental risk factors contributing to obesity in children in general, such as low socioeconomic status, unhealthy diet, and sedentary lifestyle, may also affect children with disabilities, who may be more susceptible to such factors owing to their physical, cognitive, and other functional limitations [20,21,32]. Similar to children without disabilities, children with disabilities who have excess body weight have been shown to be more likely than their healthy weight counterparts to develop additional chronic health conditions [26,33]. Thus, the current and future health consequences of obesity could be more intense for these children, who already have impairments and related functional limitations, than for children without disabilities [20].…”
Section: Introductionmentioning
confidence: 99%
“…When considering the prevalence statistics in relation to the national data, the rates for overweight and obesity are similar. However, in some studies, overweight and obesity have been found to be much greater than national data on the general populations (Phillips et al, 2014;Rimmer, Yamaki, Lowry, Wang, & Vogel, 2010;Whiteley, Dodou, Todd, & Shattock, 2004). When considering the variance in rates of overweight and obesity in the context of the great heterogeneity among ASD populations, it is difficult to reach a conclusion about the most accurate account.…”
Section: Incidence Of Obesitymentioning
confidence: 98%
“…However, when looking closer at studies by Phillips et al (2014), Rimmer et al (2010), and Whiteley et al (2004), among others, rates were based on smaller samples, and data were collected by parental report. Because of these limitations, the authors'…”
Section: Incidence Of Obesitymentioning
confidence: 99%